Knowledge Management dan Kinerja Karyawan: Tinjauan Sistematis dari Asia - Muhammad Ariq Athallah Akbar; Husna Karimah; Azizah Akbariani Ahmad (Politeknik Negeri Batam, 2025)
This study provides a comprehensive analysis of the role of Knowledge Management (KM) in enhancing employee performance through a Systematic Literature Review (SLR). In the context of a growing knowledge-based economy, organizations are increasingly required to manage information and experience in a structured manner to foster innovation, improve efficiency, and sustain competitive advantage. This review adopts the SLR protocol proposed by Williams et al, selecting 12 peer-reviewed articles from the Scopus database based on inclusion criteria including Asian geographic focus, Q1/Q2 journal rankings, and relevance to the research variables. The findings reveal that KM significantly contributes to employee performance, both directly and as a mediating variable. KM processes—such as knowledge creation, storage, sharing, and application—play a vital role in promoting productivity, innovation, and adaptability. This study contributes to the literature by mapping current trends and identifying research gaps, offering both theoretical insight and practical implications for future studies.